Revaluation and reform: Bringing council tax in England into the 21st century - Stuart Adam; Louis Hodge; David Phillips; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2020)
Council tax matters. It matters to local government as, at over 31 billion a year, it now makes up over half of its funding for non-education expenditure. It matters for households, for whom the bills take up an average of over 3% of their income. And it matters to central government, which is ultimately responsible for the sustainability and suitability of the local government finance system and, like local government, can be subject to political difficulties when the populace is unhappy with the system. Council tax bands in England are still based on property values in April 1991 - almost 30 years ago. Since then the relative prices of different properties have changed significantly: for example, official estimates suggest the average price in London is now more than six times what it was in 1995, compared with barely three times in the North East. Moreover, the most valuable properties in 1991 (Band H) attract just three times as much tax as the least valuable properties (Band A), despite being worth at least eight times as much in 1991 and typically even more now, since prices have risen most in areas where they were already highest. Council tax is therefore both increasingly out of date and arbitrary, and highly regressive with respect to property values. It is ripe for reform. This report analyses the effect of updating and reforming council tax on different local authorities (LAs) and different household types in England. This is in the context of growing concerns about both wealth and regional inequalities, especially between the North and Midlands, where property values are much lower and have risen relatively slowly since 1991, and London and the South East, where they are much higher and have risen more.
Keywords: 330; Gemeindesteuer; Grundsteuer; Steuerreform; Immobilienpreis; Steuerwirkung; England